SAT0589-HPR Body Mass Index and Its Relationship to Disease Activity in Early Rheumatoid Arthritis. (10th June 2014) - Creaser, C.; Harrison, T.; Martin, L.; Barnabe, C.
Abstract : Background: Obesity rates in Canada have increased 3% (to 25%) over the past 8 years. Obese patients develop more severe forms of many diseases and have more comorbidities develop over time. We are interested in determining if a relationship exists between the body mass index (BMI) of patients with early rheumatoid arthritis (ERA) in the first year of disease and their disease activity. This would support the need for lifestyle interventions in ERA patients to improve disease outcomes. Objectives: 1) To determine whether BMI is related to disease activity in RA in the first year of disease; 2) To determine if overweight or obese (BMI ≥25) have worse disease activity, compared to normal or underweight status. Methods: A multidisciplinary Early Inflammatory Arthritis Clinic is held at our tertiary care centre in Canada, with a catchment area of 1.5 million people. Criteria for the clinic include a referral for symmetric polyarthritis. A standardized data collection protocol captures clinical data including the DAS28, patient-reported outcomes, quality of life and function (HAQ). Patients are seen every 3 months for the first year, and are treated to a low disease activity target. Patients newly diagnosed with RA from 01/2009-12/2012 and with height and weight measurements at all visits (n=134) were included in this analysis. Patients were categorized as being normal weight (BMI 18.50-24.99), overweight (BMI 25.0-29.99) or obese (BMI ≥30). Ranked correlation tests were used to determine the relationship between BMI and HAQ, and BMI and DAS28, at each of 0, 6 and 12 months. Stratified analysis of HAQ and DAS28 scores by BMI category was performed. Results: Our cohort included 93 females and 41 males with a mean age of 52 years. At baseline the mean tender joint count (28 joints) was 11 (SD ±6.56) and mean swollen joint count (28 joints) was 8 (SD ±5.91) with a HAQ of 1.18 (SD ±0.874) and DAS28 of 5.17 (SD ±1.31). Nearly 2/3's of the cohort was overweight or obese (n=89, 63%), with a baseline mean BMI of 27.7±5.47 and was 27.8±5.96 at 12 months. There was no relationship between BMI and HAQ at baseline (p=0.986), 6m (p=0.891) or 12 m (p=0.438). There was also no relationship found between BMI and DAS28 at each visit (p=0.892, 0.447, 0.381) respectively. Stratified analysis also did not find any differences in disease activity between BMI categories. Conclusions: In our ERA cohort we did not find a relationship between BMI and disease activity at diagnosis or during the first year of treatment. A relationship may be seen with longer observation. Lifestyle modifications to reduce body weight are still important for minimizing the cardiovascular risks associated with obesity and cardiovascular disease. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4747